Microtubule-associated protein 1B rescues memory decline in Alzheimer's disease model mice - Yoshimi Mitsuyama; Tadashi Koide; Tetsuo Kanno; Shizuko Nagao; Takayuki Manabe; Fuyuki Mitsuyama (Annals of Alzheimer's and Dementia Care - Peertechz Publications, 2018)
Background: The classic pathologies seen in Alzheimer's disease (AD) are amyloid plaques and neurofibrillary tangles, but synapse and spine loss have been recognised as new pathologies. Microtubules are thought to be less plentiful in spines, so it has been thought that spine shape change and molecular transportation in spines is performed mainly by actin. However, reports of the intraspinal invasion of microtubules, alternative mechanisms require investigation. Microtubule-associated protein 1B has microtubule conserving and polymerising effects and is overexpressed in Fragile X syndrome, in which spines are thin and elongated. Fragile X protein is an mRNA-binding protein and as mRNA is transported along microtubules as RNA granules by kinesine family, we suspected that Fragile X protein is conjugated with kinesin family tail and RNA granules. As a result, the mutation of this protein may cause impairment of mRNA transport to spines. This could result in low local protein synthesis in spines that may induce thin spines, and finally inducing MAP1B overexpression by a negative feedback mechanism. As a result, intraspinal microtubules may be elongated and spines may be elongated. It is speculated that the polymerisation of these intraspinal microtubules by MAP1B may restore spine integrity and rescue AD symptoms, however, this has not yet been proven. Method: We injected a Map1b-lentivirus chimera to the hemi-hippocampus of AD-model mice. The spatial working memory was assessed by the Y-maze and compared with non-injected mice. The change in spines by MAP1B overexpression in cultured neurons was investigated.  Results: The overexpression of Map1b to the hemi-hippocampus of AD model mice rescues memory impairment. Spatial working memory assessed by the Y-maze in injected mice improved to almost normal levels within 2 days of the injection. The overexpression produced microtubule-dense remarkably enlarged spines in the cultured neurons. Map1b-lentivirus chimera injection also restored reduced postsynaptic densities in AD model mice, as assessed by protein immunoblots. Conclusions: These results suggest that MAP1B-dependent intraspinal microtubules may enhance the structural integrity of spines, restoring spine shrinkage, improving the bidirectional transportation of memory-facilitating molecules, and rescuing memory impairment in AD model mice.